2023
DOI: 10.1021/acs.est.2c08491
|View full text |Cite
|
Sign up to set email alerts
|

Nationwide Occurrence and Unexpected Severe Pollution of Fluorescent Brighteners in the Sludge of China: An Emerging Anthropogenic Marker

Abstract: Fluorescent brighteners (FBs) are a group of mass-produced dyestuff chemicals that have been extensively used for decades. However, knowledge of their occurrence in municipal wastewater treatment plants on a large geographical scale remains unknown. Herein, we implemented the first nationwide survey for wastewater-derived FBs in sludge across major cities in China. All 25 target FBs were detected in the nationwide sludge. Ionic FBs exhibited much higher concentrations than nonionic FBs. The total sludge concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 40 publications
8
6
0
Order By: Relevance
“…26 Two very recent studies from the Zeng group reported the occurrence of CBS in indoor dust and sludge collected from China. 54,55 The detected concentrations of CBS in our study were comparable to the results from the Zeng et al studies (dust: 0.059 to 4.04 μg/g; sludge: 0.013 to 8.35 μg/g). 54,55 These results demonstrated its ubiquitous presence in the environment.…”
Section: Resultssupporting
confidence: 90%
“…26 Two very recent studies from the Zeng group reported the occurrence of CBS in indoor dust and sludge collected from China. 54,55 The detected concentrations of CBS in our study were comparable to the results from the Zeng et al studies (dust: 0.059 to 4.04 μg/g; sludge: 0.013 to 8.35 μg/g). 54,55 These results demonstrated its ubiquitous presence in the environment.…”
Section: Resultssupporting
confidence: 90%
“…For TA-FRs and ∑TAs (Figure 1B,C), a clearer geographical distribution was observed with prominently higher pollution levels in the eastern coastal provinces/municipalities, followed by a mitigating pollution trend from the central provinces/municipalities toward the western ones. Consistent with previous studies, similar regionspecific spatial distributions of multiple emerging pollutants in the nationwide sludge of China were also observed for alternative halogenated flame retardants, 41 organophosphate esters, 33 fluorescent brighteners, 42 and quaternary ammonium compounds. 43 Compared with West China, East and Central China are more economically developed regions with higher degrees of industrialization and urbanization as well as population density.…”
Section: ■ Results and Discussionsupporting
confidence: 90%
“…To evaluate the anthropogenic impacts of these emerging chemicals on the natural environment via sludge disposal, we further estimated the annual influx of TA-UVFs, TA-FRs, and ∑TAs from a national perspective based on the total annual sludge production in China. According to the statistical data, approximately 14.7 million tons of dry sludge was generated in China in 2020 . Based on our measured median sludge concentrations of the two classes of triazine chemicals, the nationwide annual influx of TA-UVFs, TA-FRs, and ∑TAs in China through sludge loading can be estimated to be 2.34, 11.7, and 14.6 tons/year, respectively.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…The results of the present study were consistent with several previous studies, which found significant correlations between population density and organic contaminants, such as fluorescent brighteners and perfluoroalkyl substances. 50,51 The results of this study suggested that the occurrence of some aryl-OPEs in the soil environment might be related closely to anthropogenic activities.…”
Section: ■ Results and Discussionmentioning
confidence: 77%